Analysis of Cash Buying and Murābaḥah Financing (Case Study on Green Mutiara Housing Tambaksogra PT Graha Perwira Pratama, Kembaran Sub-District, Banyumas Regency) - Wahyuni, Sinta (Journal of Economicate Studies, 2018)
This study explores the comparative implementation of cash and Murabahah financing methods in home purchases at Green Mutiara Housing, PT Graha Perwira Pratama, Banyumas Regency. Access to housing remains a challenge for low- to middle-income communities, prompting the need to evaluate payment alternatives that align with consumer needs and Islamic financial principles. A field research approach was adopted using qualitative descriptive-comparative methods. Data collection was conducted through interviews, observation, and documentation at the housing location. The focus was on the application procedures for both cash and credit purchase systems, particularly the Murabahah financing method used through Islamic banks. The findings show that cash purchases—both hard and installment-based—offer lower prices, quicker processing, and fewer administrative requirements. Credit purchases via Murabahah involve banks paying developers upfront, followed by consumer repayments under agreed profit margins. Buyers benefit from accessible financing without needing full payment upfront, although total costs are generally higher due to margin and longer payment periods. While both payment systems are functional and widely accepted, each has distinct financial and administrative implications. Cash payment offers simplicity and immediate ownership, while credit financing provides broader accessibility. The choice ultimately depends on buyer capacity and preference, with Murabahah offering an Islamic-compliant financing alternative.